A Comparison of Behavioral Competencies Between Home Economics Specialist and Non-Specialist EPP Teachers - Marzo, Ann Justine B; Trinidad, Mary Justine Clarise A (Alipato, A Journal of Basic Education; Vol 13 (2022), 2023)
This qualitative study seeks to compare the behavioral competencies of 15 Home Economics (HE) specialist and non-specialist Edukasyong Pantahanan at Pangkabuhayan (EPP) teachers and to identify factors influencing these competencies. Data, obtained using researcher-developed Behavioral Competencies Questionnaire, were subjected to thematic analysis. Results revealed that the EPP teachers have positive self-image, positive teacher traits, clear social roles, and motivation in teaching EPP. HE specialists felt confident when teaching because they knew that they were teaching accurately. They were passionate and motivated to advocate the value of learning EPP. Non-HE specialists exerted more effort in learning EPP because of their professional commitment. They felt effective when students showed positive outcomes, but some still tended to lack depth when teaching EPP. They lost motivation sometimes because teaching EPP was forced upon them. Field of specialization was a factor influencing EPP teachers’ self-image and personality traits. Their perceived social role was molded by the nature of the profession, and their motivation by teaching preparation experiences. Based on the results, HE curricula should continue to focus on developing effective HE teachers, and more HE programs should be promoted. Demotivated EPP teachers should remind themselves of their social roles that motivate them to teach.